The acquisition of a series of phrasal verbs in the course integrated English I at the University of Costa Rica - Navas Brenes, César Alberto (Universidad de Costa Rica, 2018)
This article is aimed at observing the acquisition and assessment of a list of forty phrasal verbs in a group of first-year students of the course LM-1001 Integrated English I at the University of Costa Rica. First of all, the author implements a placement test to determine the students’ proficiency level, being Integrated English I the first EFL course of the program. Then, the author administers two instruments to assess the students’ knowledge on a series of phrasal verbs before the presentation, practice, and production throughout the second part of the semester. A contextualized sample lesson to practice a selection of phrasal verbs is also included. To finish, the students receive two additional instruments and a final evaluative instrument to observe the level of acquisition of twenty phrasal verbs as a result of explicit instruction.